Caracterização da microbiota bacteriana da água do Rio Negro em diferentes períodos sazonais - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The microorganisms of the community aquatic system of the Solimões and Negro rivers, as well as the diversity of these ecosystems have not been thoroughly investigated so far. The aim of this study was to characterize the bacterial microbiota of the Negro River in relation to seasonality, both in its quantitative aspect (forming units count colonies - CFUs) and qualitative (taxonomic identification via DNA sequencing RNA encoding small ribosomal subunit SSU -rRNA). Negro River water samples were collected at five different points on 4 and 5 depths dates from different times of the year, and all samples CFUs were counted. Total DNA was extracted from the biomass contained in the water of the Negro in full periods (N2) and receding (RN3) and analyzed spectrophotometrically and by agarose gel electrophoresis 0.8%. They were amplified variable regions V3 and V4 SSU-rRNA PCR (Reaction Polymerase Chain DNA) and the amplicons were sequenced by pyrosequencing using equipment 454 (Roche®). Files (reading DNA) of RN2 and Rio Negro RN3 libraries were submitted to the Mothur program suite for quality control, alignment of sequences, calculation of genetic distances and definition of Operational Taxonomic Units - OTUs, plus an estimate of the richness and diversity of species. The CFU count was possible to compare the number of culturable bacteria in the different collection points and due to seasonality. By molecular analysis we found that the phylum Proteobacteria proved dominant in these two collections of the river (full and low tide), the dominant genera of this phylum in full were Limnohabitans, methylomonas, and other expressive filo was Acidobacteria the GP3 race. In the ebb period abundant genera were Polynucleobacter, Acinetobacter and Curvibacter within the phylum Proteobacteria. Rarefaction curves demonstrated that RN3 library is more diverse in number of species than the RN2 library and confirmed by Shannon and InvSimpson index. It can be seen from the ACE 1 indexes and Cha RN3 the library is richer in species compared to RN2.
Keywords: Sistemas aquáticos; Bacia Amazônica; Diversidade dos procariotos; Ciclos biogeoquímicos; Filo Protobacteria; Abordagem Metagenômica; Proteobacteria; CIÊNCIAS BIOLÓGICAS: ECOLOGIA